Methods of Teaching Arab (Eurasian Scientific Herald, 2023)
Currently, the Arabic language occupies a certain place in the educational process. The purpose of this article is to consider some ways to optimize Arabic language teaching in universities. The article considers the correct choice of teaching methods and techniques, the selection of educational material taking into account the motivation of students, as compliance with the peculiarities of teaching Arabic.